Evaluation of the Impact of Coherence Protocols and Cache Sizes on Parallel Algorithms Through Simulations - Fagundes, Guilherme Dantas C.; Souza, Matheus Alcântara (Anais Estendidos do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2024: Anais Estendidos do XXV Simpósio em Sistemas Computacionais de Alto Desempenho, 2024)
This article explores the intersection between parallel algorithms and cache optimization, focusing on how different coherence protocols and cache sizes impact the performance of parallel algorithms. Through simulations, we evaluate the efficiency of parallel algorithms under various cache configurations. Our goal is to understand the implications of these configurations and identify optimal strategies for cache utilization. The results of this study provide valuable insights for computational performance optimization in the modern era of technology.